(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
The interaction between p-oxyacetophenone and a number of carbonic acids hydrazides gives corresponding alkyl (cyanoalkyl) carbonylhydrazones. The possibility of ring-chain tautomerism in obtained systems has been studied.